About the Actor’s Reality and the Things We See. Can an Actor Create Reality Through Fiction, or Does He Merely Imitate It? - HATHÁZI, András (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
In this article, award-winning stage and film actor András Hatházi challenges, from the viewpoint of his prestigious career as an artist and pedagogue, the relationship between actor, role, reality, and fiction. Can the actor create reality through fiction? In order to answer this question, the author turns towards the way children are playing, finding therein both truth, and inspiration.